The Readability Level of Reading Texts in Erlangga Straight Point Series: English for Eleventh Grade Students - Ratri Handayani; Furaidah Furaidah; Francisca Maria Ivone (Graduate School of Universitas Negeri Malang, 2020)
Abstract: This study aims to describe the readability level of reading texts in ESPS: English for the 11th grade students. The measurement tools were Coh-Metrix RDL2, Miyazaki EFL Reading Index and teachers’ professional judgment. The formula were effective in measuring the texts readability by calculating the number of words, letters, and sentences in the text. The Score of Coh-Metrix RDL2 showed that the reading texts was easier for reading level of 11th graders. MEFLRI claimed that reading texts in ESPS textbook are match for reading level of 11th graders. Teachers’ judgment claimed, the texts were suitable for eleventh grade students.Abstrak: Penelitian ini bertujuan untuk mendeskripsikan tingkat keterbacaan 19 teks bacaan dalam ESPS: English untuk siswa kelas 11. Tiga alat ukur digunakan untuk mengukur tingkat keterbacaan yakni Coh-Metrix RDL2 dan Miyazaki EFL Reading Index, dan penilaian guru. Kedua formula terbukti efektif dalam mengukur keterbacaan teks dengan menghitung total huruf, kata, dan kalimat dalam teks. Coh-Metrix menunjukkan bahwa teks bacaan lebih mudah dipahami oleh siswa pada kelas 11, sedangkan MEFLRI menunjukkan bahwa teks bacaan sangat cocok diberikan pada kelas 11. Penilaian guru menyatakan teks bacaan sesuai untuk siswa kelas 11.